The Basolateral Amygdala GABAergic System in Health and Disease - Prager, Eric M (J Neurosci Res, 2015)
The brain comprises an excitatory/inhibitory neuronal network that maintains a finely tuned balance of activity critical for normal functioning. Excitatory activity in the basolateral amygdala (BLA), a brain region that plays a central role in emotion and motivational processing, is tightly regulated by a relatively small population of gamma-aminobutyric acid (GABA) inhibitory neurons. Disruption in GABAergic inhibition in the BLA can occur when there is a loss of local GABAergic interneurons, alterations in GABA(A) receptor activation, or dysregulation of mechanisms that modulate BLA GABAergic inhibition. Disruptions in GABAergic control of the BLA emerge during development, in aging populations, or after a trauma, ultimately resulting in hyperexcitability. BLA hyperexcitability manifests behaviorally as an increase in anxiety, emotional dysregulation, or the development of seizure activity. This article reviews the anatomy, development, and physiology of the GABAergic system in the BLA, and circuits that modulate GABAergic inhibition, including the dopaminergic, serotonergic, noradrenergic, and cholinergic systems. We highlight how alterations in various neurotransmitter receptors, including the acid sensing ion channel 1a (ASIC1a), cannabinoid receptor 1 (CB1), and glutamate receptor subtypes, expressed on BLA interneurons, modulate GABAergic transmission and how defects of these systems affects inhibitory tonus within the BLA. Finally, we discuss alterations in the BLA GABAergic system in neurodevelopmental (autism/Fragile X syndrome) and neurodegenerative (Alzheimer’s disease) diseases, and after the development of epilepsy, anxiety, and traumatic brain injury. A more complete understanding of the intrinsic excitatory/inhibitory circuit balance of the amygdala and how imbalances in inhibitory control contribute to excessive BLA excitability will guide the development of novel therapeutic approaches in neuropsychiatric diseases.